2007
DOI: 10.1111/j.1365-2230.2007.02513.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical kinetin 0.1% lotion for improving the signs and symptoms of rosacea

Abstract: Many patients with rosacea are unable to tolerate extended treatment periods with topical agents because of the unusually high skin sensitivity that often accompanies rosacea. Kinetin (N(6)-furfuryladenine) is a plant cytokinin that reportedly helps restore skin barrier function and may be useful to ameliorate the signs and symptoms of rosacea. The purpose of this open-label study was to determine the tolerance and efficacy of twice-daily application of kinetin 0.1% lotion for improving the signs and symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 10 publications
(24 reference statements)
0
17
0
3
Order By: Relevance
“…It has been extensively used as growth promoting hormone in plant tissue culture systems [1, 2] but the potential effects of kinetin on human health are still under research. Some studies reported an effect of kinetin on human disorders or diseases [58]. Examples are prevention of age-related changes in human skin, presumably by protecting the DNA in skin cells from damage and by decreasing skin water loss [5, 8] as well as the therapeutic potential of kinetin in the treatment of the human splicing disease familial dysautonomia, a genetic disorder affecting the nervous system [6, 9].…”
Section: Introductionmentioning
confidence: 99%
“…It has been extensively used as growth promoting hormone in plant tissue culture systems [1, 2] but the potential effects of kinetin on human health are still under research. Some studies reported an effect of kinetin on human disorders or diseases [58]. Examples are prevention of age-related changes in human skin, presumably by protecting the DNA in skin cells from damage and by decreasing skin water loss [5, 8] as well as the therapeutic potential of kinetin in the treatment of the human splicing disease familial dysautonomia, a genetic disorder affecting the nervous system [6, 9].…”
Section: Introductionmentioning
confidence: 99%
“…45 Another topical therapy that has been shown to help restore the skin's barrier is kinetin, a plant cytokinin that is available as a 0.1% lotion. 46 The Chinese herb Chibixiao has also been found helpful in the treatment of rosacea in at least one trial. 47 In addition, patients with rosacea should be counseled to adhere closely to their therapy, and to avoid triggering factors.…”
Section: Oral Therapy Antibioticsmentioning
confidence: 99%
“…The applications for such adjuvant treatments are subtypes 1 and 2 [48,49]. Some open questions remain.…”
Section: Treatment Of Rosaceamentioning
confidence: 99%